PENGARUH DUKUNGAN KELUARGA TERHADAP TINGKAT AKTIVITAS SEHARI-HARI LANSIA PASCA STROKE NON HEMORAGIK PUSKESMAS LUBUK BUAYA - Fidiariani Sjaff,; Rasti Andika Sari,; Mashdarul Ma’arif, (Nusantara Hasana Journal, 2026)
Following a stroke, elderly individuals often experience increased dependence on others, resulting in reduced independence in performing activities of daily living (ADL). Consequently, post-stroke care requires substantial family involvement and support. This study aimed to examine the effect of family support on the level of daily activities among elderly patients after non-hemorrhagic stroke at Puskesmas Lubuk Buaya Padang. This research was conducted within the fields of geriatrics (Internal Medicine) and neurology in November 2023. An observational study with a cross-sectional design was employed, utilizing secondary data obtained from questionnaires and medical records. A purposive sampling technique was applied, and a total of 30 elderly respondents were included in the analysis. Univariate analysis was presented as frequency distributions, while bivariate analysis was performed using the chi-square test. The results demonstrated that the majority of respondents received high levels of family support (83.3%), while the remaining participants received moderate levels of support (16.7%). In addition, most elderly patients exhibited good levels of daily activity (86.6%), whereas 13.3% demonstrated moderate activity levels. Statistical analysis revealed a significant association between family support and the level of daily activities among elderly patients after non-hemorrhagic stroke (p = 0.01). In conclusion, elderly patients with non-hemorrhagic stroke at Puskesmas Lubuk Buaya Padang generally receive high family support, which is significantly associated with better performance of daily activities.